1996
DOI: 10.1177/0310057x9602400514
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from Mivacurium Block with or without Anticholinesterase following Continuous Infusion in Obstetric Patients

Abstract: Neostigmine antagonism after suxamethonium followed by mivacurium chloride bolus and infusion was studied. Thirty ASA group I or II patients were given mivacurium 0.15 mg/kg followed by infusion during nitrous oxide-enflurane-pethidine anaesthesia. Train of four (TOF) stimuli were applied to the ulnar nerve at the wrist and TOF twitch height and ratio measured by TOF-GUARD nerve stimulator. Mivacurium infusion was titrated to give a 90% block of first twitch height. Patients were randomized into two groups. Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Sixteen randomized controlled studies with data from 546 patients were included . Six studies compared spontaneous recovery with both neostigmine and edrophonium reversal .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sixteen randomized controlled studies with data from 546 patients were included . Six studies compared spontaneous recovery with both neostigmine and edrophonium reversal .…”
Section: Resultsmentioning
confidence: 99%
“…Six studies compared spontaneous recovery with both neostigmine and edrophonium reversal . Five studies compared spontaneous recovery with neostigmine reversal and five studies compared spontaneous recovery with edrophonium reversal No studies on pyridostigmine were included. The overall assessment of the risk of bias for individual studies resulted in three studies judged as high quality, 11 as acceptable and two as low (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mean recovery index (T1 25-75%) of pancuronium and atracurium was twice and four times respectively, when comparing to the values presented by CULLEN (1996) with the dosage of 82-140µg/kg of pancuronium (T1=50%) and 70-85µg/kg of atracurium (T1=100%). The time points chosen for this study were established in recent human medical studies with muscle relaxants (JENSEN et al, 1993;HODGES, 1996;ANSERMINO, 1996;JAN et al, 1996; -*** 72.5 58.4 SD: standard deviation *: did not reach a T1=0 **: did not decrease the T1 under 25% ***: did not lower its TOF ratio below 0.7 Figure 2 -Mean values of time for onset (T1 = 0), clinical duration of action (T1 = 25%), recovery index (T1 25-75%) and action time (TOF=0.7) of the muscle relaxants pancuronium (5 animals) and atracurium (7 animals) given intravenously to horses. al., 1996;LLLWITZ et al, 1997;HANS et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies made in human medicine comparing the TOF-Guard with the Myograph 2000, showed that there is a very close positive correlation between the values of T1 (control twitch height), the TOF ratio and PTC, simultaneously measured by both methods (UEDA et al, 1994;MELLONI, 1995). However, other studies suggested that the TOF-Guard should not be used interchangeably with the Myograph because of a wide limit of agreement between the two monitors (MCCLUSKEY et al, 1997;LOAN et al, 1995) Recent studies had been performed using the TOF-Guard to evaluate different nondepolarizing neuromuscular blocking agents in children (HODGES, 1996;ANSERMINO, 1996) and adults (JENSEN et al, 1993;JAN et al, 1996;HANS et al, 1996;LLLWITZ et al, 1997;HANS et al, 1997).…”
Section: Introductionmentioning
confidence: 99%